Baseline characteristics and clinical features of patients with heart failure with reduced ejection fraction: a European real-world, non-interventional registry study. (25th November 2020) - Zeymer, U; Lund, L.H; Barrios, V; Fonseca, C; Clark, A.L; Damy, T; Drozdz, J; Kalus, S; Koch, C; Maggioni, A
Abstract: Background: Heart failure (HF) is a major medical and economic burden that is often managed in office based practices. Recently, the angiotensin receptor neprilysin inhibitor (ARNI) sacubitril/valsartan (S/V) was introduced as novel therapeutic option into European guidelines for the management of HF. The ARIADNE registry aims to provide information on how outpatients with HF with reduced ejection fraction (HFrEF) are managed in Europe, in light of this novel treatment option. Methods: ARIADNE was a prospective registry of patients with HFrEF treated by office-based cardiologists (OBC) or selected primary care physicians (recognized as HF specialists; PCP) in a real world setting. HFrEF patients were included prospectively, independently of whether treatment had been changed recently or not. 9069 patients were recruited from 687 centres in 17 European countries. Results: The mean age of all patients was 68.1 years (S/V: 67.3 years, Non-S/V: 68.9 years). The majority of patients were in NYHA class II (61.3%), or NYHA class III (37.1%) overall, while more patients in the S/V group showed NYHA class III (S/V: 42.8%, Non-S/V: 30.9%). Mean LVEF was slightly lower in the S/V group than in the Non-S/V group (S/V: 32.7%, Non-S/V: 35.4%, overall 34.0%). The most frequently observed signs of HF were dyspnoea upon effort, followed by fatigue, palpitations on exertion at baseline. More patients tend to have more severe symptoms in the S/V groups (e.g. for dyspnoea on effort, Non-S/V: moderate 40.8%, severe 8.6%; S/V: moderate 46.4%, severe 14.1%). 44.0% of patients from the S/V group and 39.3% of non-S/V patients reported at least one hospitalization within 12 months prior to baseline, of which 73.3% in S/V and 69.9% in non-S/V patients were due to HF., At baseline, 44.7% of the patients used a CV device, of which most were implantable cardioverter defibrillator (ICD: Non-S/V 54.2%, S/V: 52.8%), implantable cardioverter defibrillator (CRT-ICD:Non-S/V 21.9%, S/V: 27.0%), and pacemaker (Non-S/V: 13.4%, S/V: 10.5%). The mean KCCQ overall summary score was 62.6 in the S/V group and 69.5 in the Non-S/V group at baseline. 83.9% of patients were treated with ARB or ACEi in Non-S/V group, (ACEi 57.3%, ARB 26.9%). The most frequently taken drug combinations in either group were ACEi/ ARB or S/V with β -blockers (Non-S/V 69.3%, S/V 67.3%). 40.2% in the Non-S/V group and 42.9% in S/V groups used a combination of ACEi/ARB or S/V, β-blocker and MRA. Conclusions: The ARIADNE prospective registry provides insights and reflects variations in HF treatment practices in outpatients in Europe and the way S/V was introduced by OBCs and specialized PCPs in a real-world setting. In the observed population, S/V is more often prescribed to slightly younger patients with slightly lower LVEF, there was a greater observed percentage of S/V patients NYHA class III, with lower quality of life measurements and with more severe symptoms and recent hospitalizations for heart failure. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Novartis Pharma AG